Beneficial impact of first‐line mogamulizumab‐containing chemotherapy in adult T‐cell leukaemia‐lymphoma. (24th May 2022) - Shichijo, Takafumi; Nosaka, Kisato; Tatetsu, Hiro; Higuchi, Yusuke; Endo, Shinya; Inoue, Yoshitaka; Toyoda, Kosuke; Kikukawa, Yoshitaka; Kawakita, Toshiro; Yasunaga, Jun‐ichirou; Matsuoka, Masao
Summary: Chemotherapy in combination with mogamulizumab (Mog) was approved in Japan in 2014 for untreated aggressive adult T‐cell leukaemia‐lymphoma (ATL), but the survival benefit remains unclear. Therefore, we retrospectively analysed clinical outcomes in 39 transplant‐ineligible patients with untreated aggressive ATL at Kumamoto University Hospital between 2010 and 2021. The probability of four‐year overall survival was 46.3% in the first‐line Mog‐containing treatment group compared to 20.6% in the chemotherapy‐alone group ( p = 0.033). Furthermore, this survival benefit was observed even in the elderly. In conclusion, first‐line Mog‐containing treatment can be a promising strategy for transplant‐ineligible patients with ATL, especially in the elderly.